Biodegradable electronics: cornerstone for sustainable electronics and transient applications. Issue 24 (18th May 2016) - Tan, Mein Jin; Owh, Cally; Chee, Pei Lin; Kyaw, Aung Ko Ko; Kai, Dan; Loh, Xian Jun
Abstract : Electronic devices have become ubiquitous in modern society and are prevalent in every facet of human activities. Abstract : Electronic devices have become ubiquitous in modern society and are prevalent in every facet of human activities. Although electronic devices have brought much convenience and value, the insatiable appetite for newer and more attractive devices has also created a growing ecological problem: managing electronic waste or e-waste. As the lifetime of electronic devices gets shorter and shorter, the pressure on e-waste management systems is mounting with no abate in sight. Therefore, an alternative to traditional electronics must be sought. Bio-degradable electronics have thus emerged as the most viable and ideal replacement to address the issue of uncontrollable e-waste. Bio-degradability will ensure that the waste generated will be at least non-toxic and even environmentally friendly. Furthermore, bio-degradable organic materials have also been shown to be biocompatible and human-friendly, being able to be metabolized safely in the body without causing adverse physiological reactions. As such, this developing class of "green" electronics is not only able to alleviate the growing e-waste problem, but also fulfils niche applications interfacing with the human body. This Review will introduce various bio-degradable organic materials that can serve as substitutes for the different components of an electronic device, highlight recent research achievements and applications in implementing such bio-degradable devices as well as present an overview of the printing technologies available that provide the low-cost and high throughput advantages of solution-processable organic materials over the traditional inorganic materials.